1994
DOI: 10.2106/00004623-199401000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of tibial fracture-healing by non-invasive, low-intensity pulsed ultrasound.

Abstract: Sixty-seven closed or grade-I open fractures of the tibial shaft were examined in a prospective, randomized, double-blind evaluation of use of a new ultrasound stimulating device as an adjunct to conventional treatment with a cast. Thirty-three fractures were treated with the active device and thirty-four, with a placebo control device. At the end of the treatment, there was a statistically significant decrease in the time to clinical healing (86 ± 5.8 days in the active-treatment group compared with 114 ± 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
440
0
50

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 847 publications
(502 citation statements)
references
References 8 publications
12
440
0
50
Order By: Relevance
“…Our study uses a therapeutic dose roughly 10 times the intensity of the ultrasound currently being investigated to accelerate fracture repair [6,7,15]. A study by Spadaro et al [13] demonstrated that application of 30 mW/cm2 ultrasound to growing knee joints in rats showed no significant changes in long bone growth or physeal histology.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Our study uses a therapeutic dose roughly 10 times the intensity of the ultrasound currently being investigated to accelerate fracture repair [6,7,15]. A study by Spadaro et al [13] demonstrated that application of 30 mW/cm2 ultrasound to growing knee joints in rats showed no significant changes in long bone growth or physeal histology.…”
Section: Discussionmentioning
confidence: 96%
“…The original studies of the effects of ultrasound on growing bone only utilized high-intensity ultrasound (2-2.5 W/cm2) [3] and recent studies are mainly concerned with using ultrasound doses in the milliwatt range [6,7,13,14]. However, as this study does not follow these animals to physeal closure, it is unclear as to whether the histological changes reported would cause significant growth disturbances following growth plate closure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations